Globalization and Empire: Market integration and international trade between Canada, the United States and Britain, 1750-1870 - Maja Uhre Pedersen; Vincent Geloso; Paul Sharp (European Historical Economics Society (EHES), 2020)
Previous work has demonstrated the potential for wheat market integration between the US and the UK before the 'first era of globalization' in the second half of the nineteenth century. It was however frequently interrupted by policy and 'exogenous' events such as war. This paper adds Canada to this story by looking at trade and price data, as well as contemporary debates. We find that she faced similar barriers to the US, and that membership of the British Empire was therefore not a great benefit. We also describe the limitations she faced accessing the US market, in particular after American independence. Transportation costs do not appear to be the main barrier to the emergence of a globalized economy before around 1850.
Keywords: N51; N53; N71; N73; 330; British Empire; Canada; globalization; market integration; United Kingdom; United States; wheat